Spectral Induced Polarization of Biochar in Variably Saturated Soil - Gao, Z. (2020)
The measured SIP spectra as a function of saturation were interpreted by fitting a Cole–Cole model to the low‐frequency part of the SIP measurements. The porous nature of the biochar particles strongly affected the SIP response of the partially saturated sand–biochar mixtures. Due to the high residual water content of the biochar in a dry background, the relationship between bulk electrical conductivity and water saturation was nonlinear in a log–log representation. This nonlinear behavior could adequately be explained with a dielectric mixing model that considered the drainage of the biochar particles. Both the measured phase and chargeability of the sand–biochar mixtures showed a complex dependence on water saturation. This was attributed to the decrease in polarization strength of the biochar particles with desaturation and the simultaneous increase in phase of the sand background. Overall, the results of this study suggest that field SIP measurements may be a promising tool for the characterization and monitoring of biochar amendments to agricultural soils.